PENGARUH MEDIA PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR SISWA KELAS IV SD - Siti Umi Hafidho; Satrio Wibowo; Ery Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The decline in academic achievement in Indonesia, which is now a concern for many educators, is the driving force for this research. One of the things that prevents education from being better is the large number of subjects and the amount of material that needs to be studied for each subject. As a result, the teaching and learning process cannot run as smoothly as expected. Researchers take advantage of this challenge to produce media that can attract students to take part in the learning process. The final aim of this research is to find out how the mind map learning media influences students' learning creativity and how they respond to using mind map media. The Pre-Experimental Design approach was applied in this research. The Pre-Experimental Design approach was applied in this study. According to the findings, the experimental class's average learning outcome was 93.75, or 95.65%, whereas the control class's average learning outcome was 61.50, or 77.86%. These findings demonstrate that employing mind mapping media has improved student learning and had a very positive impact on fourth-grade primary school children.